Design and Assessment of a Virtual Underwater Multisensory Effects Reproducing Simulation System - Cheol-Min Kim; Jae-Hong Youn; Yoo-Kang Ji; Dong-You Choi (International Journal of Distributed Sensor Networks, 2014)
With current developments in virtual reality technology and advances in the marine industry, various virtual underwater simulation systems that help users to indirectly experience the marine environment via a variety of virtual contents are being developed. In general, underwater simulation systems that use virtual reality developed using three-dimensional graphics technology. Therefore, they are limited in terms of their ability to imbue users with a sense of immersion and presence. In addition, the expansion of the sensory range, with which users can actually experience various underwater environmental phenomena while they are in underwater simulations, is still insufficient. This paper proposes an immersive multisensory effect reproduction system that provides an improved sense of underwater reality for users. The results of comparative user evaluation tests conducted regarding the sense of reality imbued with our proposed system indicate that its sensory presence effect is superior to that of conventional systems.